Life and scientific activities of prof. Dr. Ireneusz Michalski - Kapica, Zdzisław (Anthropological Review, 1975)
Prof. dr. I. Michalski died unexpectedly during work in the Chair of Anthropology at Łódż University in January 14th 1965. This memoir describes his scientific career, results of his studies and main attainments. The author stresses contributions of I. Michalski to taxonomy, in particular creation of so called method of comparative morphology. Furthermore publications of I. Michalski are listed together with papers unpublished due to loss of manuscripts during the II World War and incomplete preparation at the time of death.